2009
DOI: 10.1136/jech.2008.086348
|View full text |Cite
|
Sign up to set email alerts
|

Risk of suicide among operated and non-operated patients hospitalised for peptic ulcers

Abstract: Hospitalised patients with gastric ulcer or duodenal ulcer have an increased risk of suicide regardless of surgical treatment. These patients, especially women, are at very high risk during the first year after first hospitalisation/operation. The evaluation and management of suicidal thoughts in patients in medical settings should be further considered.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 38 publications
1
2
0
Order By: Relevance
“…In this study, we determined that the risks of ulcer disease, pneumonia, and other forms of heart disease were significantly increased among adolescent suicide victims. The association between ulcer disease and suicide is consistent with previous data revealing a 60–70% excess risk of death due to suicide among adult patients hospitalized for peptic ulcers (Bahmanyar et al, 2009). Moreover, ulcer disease has been proposed to be strongly associated with stress and anxiety (Goodwin & Stein, 2002; Levenstein, Rosenstock, Jacobsen, & Jorgensen, 2015), partially explaining the high suicidality in this population.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In this study, we determined that the risks of ulcer disease, pneumonia, and other forms of heart disease were significantly increased among adolescent suicide victims. The association between ulcer disease and suicide is consistent with previous data revealing a 60–70% excess risk of death due to suicide among adult patients hospitalized for peptic ulcers (Bahmanyar et al, 2009). Moreover, ulcer disease has been proposed to be strongly associated with stress and anxiety (Goodwin & Stein, 2002; Levenstein, Rosenstock, Jacobsen, & Jorgensen, 2015), partially explaining the high suicidality in this population.…”
Section: Discussionsupporting
confidence: 92%
“…The present study demonstrated that adolescent suicide victims had an increased risk of several physical illnesses 3 months before suicide; this finding is consistent with that of a previous study (Ahmedani et al, 2017). Studies have reported the association of several physical illnesses, including epilepsy, asthma, migraine, concussion, infection, and peptic ulcer disease, with an increased risk of suicide behavior (Bahmanyar, Sparen, Rutz, & Hultman, 2009; Fralick et al, 2019; Lund-Sorensen et al, 2016; Singhal, Ross, Seminog, Hawton, & Goldacre, 2014). In this study, we determined that the risks of ulcer disease, pneumonia, and other forms of heart disease were significantly increased among adolescent suicide victims.…”
Section: Discussionmentioning
confidence: 99%
“…Many medical conditions have been associated with an increased risk for suicide, but these conditions have generally not been included in suicide risk assessment tools. These conditions include gastrointestinal conditions [25] , [26] , cardiopulmonary conditions [27] , [28] , [29] , [30] , oncologic conditions [31] , [32] , [33] , and pain conditions [34] , [35] . Finally, some research has emerged that links care processes to suicide risk.…”
Section: Discussionmentioning
confidence: 99%